A High-Performance Nonenzymatic Urea Sensor Based on Graphene-NiO-Polyaniline. Issue 6 (5th April 2019) - Xie, Aijuan; Du, Jiawen; Zhang, Jie; Xiong, Zhichen; Shao, Fei; Luo, Shiping
Abstract : A novel graphene-NiO-polyaniline (Gr-NiO-PANI) was prepared by electrolysis, electrodeposition and electropolymerization methods, respectively. The X-ray diffraction (XRD) proved the successful preparation and composition of the Gr-NiO-PANI hybrid. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used to further determine the structure and morphology of as-prepared composites. Cyclic voltammetry confirmed that Gr-NiO-PANI composite had excellent detection effect on urea. By comparing the electrochemical behavior of Gr-NiO-PANI with Gr-NiO and Gr-PANI modified electrodes toward urea, the role of NiO in composite and the detection mechanism of urea were explored. A common linear sweep voltammetry technique was used to detect urea. The test results showed that urea exhibited a good response on the Gr-NiO-PANI modified electrode. In the range of 60∼160 μM urea concentration, the response current of the Gr-NiO-PANI modified electrode is proportional to the urea concentration, and the concentration stand curve equation was I(μA) = −0.0886C(μM) + 58.39 (R 2 = 0.9917). The as-fabricated sensor exhibited high sensitivity (1.266 μA/μM), lower limit of detection (7.35 μM), excellent reproducibility, and so it can provide a simple and cheap method for detection of urea in environmental monitoring, agriculture, medical industry.